Stability of n- Dimensional Additive Functional Equation in Fuzzy Normed Spaces - Arasu, V.; Angayarkanni, M. (Sarajevo Journal of Mathematics, 2022)
In this paper, the authors investigate the generalized Hyers-Ulam-stability of new n- dimensional additive functional equation \[ _j=1^n f(-x_j+_1≤ i≤ n, i eq j x_i)=(n-2)_j=1^n f(x_j) \] in fuzzy normed space using direct and fixed point approach.